Mobile Application Calculator for Inverse Method and Cramer's Rule at Polytechnic Kota Kinabalu - R. H. A. Rahim; A. Baharum; M. H. A. Hijazi (2018)
Initiatives have been taken to create mobile applications for teaching and learning purposes with developing Mobile Calculator Inverse Method and Cramer's Rule. The focus is for student DBM1013 Engineering Mathematics 1 at Polytechnic Kota Kinabalu for Topic 4 Matrix and subtopic 4.3 Simultaneous Linear Equations. Students always do mistakes, less motivated and less confident, this is because the step to solve this question is complicated and related to each other. Students also cannot check their answers whether is correct or not until the calculation is completed. To test the effectiveness of this application, pre-test and post-test has been given to 39 students in the current semester. Result shows that there was an increase in student achievement which is, before using mobile calculator application is only 11 students achieved score 50-100 for pre-test while after using the application, 36 students score 50-100 marks for post-test questions.